Assessment of Heavy Metal Pollution in Seawater, Suspended Particulate Matter, Algal Mat, Sediment and Gastropod (Nerita Lineata) in Dumai Coastal Waters, Sumatra, Indonesia - Amin, Bintal (2009)
Concentrations of Cd, Cu, Pb, Zn, Ni and Fe in the surface seawater, suspended particulate matter, algal mat, sediments and gastropod Nerita lineata were determined to assess the status of heavy metal pollution in Dumai coastal waters. Concentrations of heavy metal in sediments varied from 0.88, 6.08, 32.34, 53.89, 11.48 μg/g dry weight and 3.01 % for Cd, Cu, Pb, Zn, Ni and Fe, respectively. These concentrations were comparable to metal concentrations in non polluted coastal waters and even lower than concentrations found in the sediments from the west coast of Peninsular Malaysia which is located just at the opposite side of the study area by the Malacca Straits. Generally, higher metal concentrations in the surface seawater, suspended particulate matter, algal mat, sediment and gastropod Nerita lineata were found at the stations with more industrial and anthropogenic activities near Dumai city center (eastern and central regions). Metal pollution index (MPI) of N. lineata further confirm higher level of heavy metal contaminations at the eastern region of Dumai coastal waters. Cd in sediments from the eastern region was the only metal that slightly higher than effective range low (ERL) but still below effective range medium (ERM) values. The enrichment factor (EF) and pollution load index (PLI) values for Cd and Pb in the eastern region were also higher than other regions. Index of geoaccumulation (Igeo) indicated that most of the stations were categorized as class 1 (unpolluted to moderately polluted environment) and only Cd in Cargo Port was in class 2 (moderately polluted). More than 50 % of Cd, Cu, Pb, Zn, Ni and Fe in sediments were accumulated in the ‘resistant’ fraction which indicated that the mobility of these metals in Dumai coastal waters were quite low. The eastern and center regions of Dumai coastal waters accumulated higher percentages of ‘nonresistant’ fraction of metals, especially Pb. However, only Pb in the eastern region was dominated by ‘nonresistant’ fraction (> 60 %). For overall stations, Pb also showed the highest percentage (45.32 %) of ‘non-resistant’ fraction, suggesting more anthropogenic inputs of Pb in Dumai coastal waters in comparison with other metals (43.22, 40.85, 37.34, 25.93 and 18.03 % for Cd, Zn, Ni, Cu and Fe, respectively). All biomonitor organisms analyzed in the present study showed their ability to accumulate metals from their environment. T. telescopium accumulated the highest concentrations of Cd, Cu and Pb, whilst N. lineata accumulated the highest concentration for Zn. However, the difference between concentrations of Cd, Cu and Pb in both species was not significant and T. telescopium was not widely distributed in Dumai coastal waters as for N. lineata. Furthermore, among the studied biomonitors, N. lineata has wider range of distribution in the study area and it also fulfilled some of the prerequisites for being indicator organisms for heavy metal pollution. The mean concentrations of Cd, Cu, Pb, Zn, Ni and Fe in N. lineata were 4.14, 5.90, 44.43, 3.74, 20.73, 24.91 μg/g in shell; 4.16, 7.31, 51.78, 17.63, 23.52, 30.60 μg/g in operculum and 0.71, 15.16, 9.34, 94.69, 5.08, 397.96 μg/g d.w in the total soft tissue, respectively. Concentrations of Cd, Pb and Ni decreased in the order: operculum > shell > soft tissue whilst Cu, Zn and Fe in the order of soft tissue > operculum > shell. Metal concentrations, especially Cd in the shells and Pb in the soft tissues of N. lineata were significantly correlated with some of the respective geochemical fractions of metal concentrations in sediment as well as with metal concentrations in algal mat, suspended particulate matter and seawater which suggest that N. lineata could be used as biomonitoring agent for heavy metals pollution in Dumai coastal waters. Geochemical fractionation analysis and calculated pollution indices using surface sediments and gastropod N. lineata revealed that Dumai coastal waters can be classified as unpolluted to moderately-polluted coastal environment. Therefore, although Dumai coastal waters is still not seriously polluted, a continuous environment monitoring program should be implemented as the ever increasing human activities and rapid developments in many infrastructures and industry sectors are continuously expanding.